Kemampuan Representasi Matematis Siswa SMP Kelas VIII pada Materi Sistem Persamaan Linear Dua Variabel dengan Pendekatan Kontekstual - Ajeng Siti Rohmah; Euis Eti Rohaeti; muhammad Afrilianto (LP2M Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to examine the improvement of students' representation ability of Class VIII on the material of two-variable linear equation system through contextual approach. This type of research is classroom action research. The method of this research is qualitative descriptive. This research was conducted on Grade VIII-A students of SMP Mahardhika in the academic year 2017/2018 with 39 students. The instrument used is a student's mathematical representation test, cycles I and II tests (after giving of action), and an observation sheet for teachers and students to conditions of action implementation. The results of this study indicate that the aspect of mathematical representation ability of students has increased because of the problems tested in each test, the more students who score above the KKM. Based on the work indicator, it is concluded that the mathematical representation ability of grade VIII-A students of SMP Mahardhika Batujajar on two-variable linear equation system can be improved through contextual approach.